2023
DOI: 10.3390/plants12030433
|View full text |Cite
|
Sign up to set email alerts
|

Ascophyllum nodosum and Silicon-Based Biostimulants Differentially Affect the Physiology and Growth of Watermelon Transplants under Abiotic Stress Factors: The Case of Salinity

Abstract: Salinization of cultivated soils is a global phenomenon mainly caused by agricultural practices and deteriorates plant production. Biostimulants are products which can be applied exogenously to enhance the plants’ defense mechanism and improve their developmental characteristics, also under abiotic stresses. We studied the potential of two biostimulants, Ascophyllum nodosum (Asc) seaweed and a silicon-based (Si), to alleviate the saline conditions endured by watermelon transplants. Three salinity (0 mM, 50 mM,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…Similarly, Subramaniyan et al [90] recorded a 67.8% yield increase when 5.0 L ha −1 of A. nodosum was applied as soil drenching. Yield increase following A. nodosum application, also recorded for other horticultural crops such as sweet pepper [91], pea [92], and watermelon [93], can be attributed to increased assimilation of N use [94] and the stimulation of endogenous hormone homeostasis through the presence of polysaccharides [95]. PGPRs have also been proven to increase tomato yield.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, Subramaniyan et al [90] recorded a 67.8% yield increase when 5.0 L ha −1 of A. nodosum was applied as soil drenching. Yield increase following A. nodosum application, also recorded for other horticultural crops such as sweet pepper [91], pea [92], and watermelon [93], can be attributed to increased assimilation of N use [94] and the stimulation of endogenous hormone homeostasis through the presence of polysaccharides [95]. PGPRs have also been proven to increase tomato yield.…”
Section: Discussionmentioning
confidence: 95%
“…For chlorophyll content, the W1 treatment recorded the highest amounts of individual (e.g., a and b chlorophyll) and total chlorophyll content (0.06, 0.08 and 0.14 mg/100 g dw, respectively), and was significantly different from the rest of the treatments. The high contents of chlorophylls for the W1 treatment are probably associated with the positive effects of Si application on the photosynthetic apparatus of plants, since several studies have reported the increase of chlorophylls and carotenoids after Si application [41,83,96,97]. However, considering that in most of the studies, Si is applied as a stress alleviation measure that protects chloroplasts from oxidative stress and the fact that all the treatments in our study contained Si, our findings could be correlated with the number of biostimulant applications, suggesting that more than one application might not have a positive effect on plants grown under non-stressful conditions.…”
Section: Carotenoid and Chlorophyll Contentmentioning
confidence: 99%
“…Similarly, the use of seaweed extracts (Ascophyllum nodosum) also improved the crop yield of watermelon plants, whereas a variable effect on quality parameters was suggested depending on the biostimulant application regime and dose. The same type of biostimulants also had a positive effect on alleviating the negative impact of drought stress on watermelon transplants [41]. On the other hand, Soteriou et al [42] suggested that the application of protein hydrolysates did not affect yield parameters, and most of the fruit quality features assessed in grafted watermelon plants were due to the high vigor of the rootstock, which concealed any impacts of the biostimulant formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Las algas marinas, es otro bioestimulante considerado como una excelente fuente de polisacáridos, glicerol, micro y macro nutrientes (El Khattabi et al, 2023), así como hormonas de crecimiento, los cuales favorecen el desarrollo de las plantas (Pérez, López, & Reyes, 2020). Los estudios anteriores destacan la utilidad de los bioestimulantes para el rendimiento, especialmente por el beneficio de asimilar nutrientes en el cultivo que influyen sobre la producción (Bustamante González et al, 2022), como el uso de bioestimulante a base de Silicio los cuales ayudan a disminuir la influencia de la salinidad sobre los cultivos (Bantis & KouKounaras, 2023) o como herramientas modernas para la agricultura (Hung et al, 2023). Los resultados de la investigación apuntan a la eficacia de los bioestimulantes, contribuyendo a reducir los daños en las plántulas de cacao en vivero, mejorar la supervivencia y para aumentar la productividad.…”
Section: Introductionunclassified